Systematic literature review and meta-analysis of cardiovascular risk factor management in selected Asian countries - Eric J Yeh; Ruth Bartelli Grigolon; Sarah Ramalho Rodrigues; Ana Paula A Bueno (Becaris Publishing Limited, 2023)
Aim: There is a need to understand the management status of hypertension, dyslipidemia/ hypercholesterolemia, and diabetes mellitus in the Asia-Pacific region (APAC). Methods: We conducted a systematic literature review and meta-analysis to summarize the awareness, treatment, and/or control rates of these risk factors in adults across 11 APAC countries/regions. Results: We included 138 studies. Individuals with dyslipidemia had the lowest pooled rates compared with those with other risk factors. Levels of awareness with diabetes mellitus, hypertension, and hypercholesterolemia were comparable. Individuals with hypercholesterolemia had a statistically lower pooled treatment rate but a higher pooled control rate than those with hypertension. Conclusion: The management of hypertension, dyslipidemia, and diabetes mellitus was suboptimal in these 11 countries/regions.